Improved flow direction algorithm for WSN coverage optimization - CHEN Wei; YANG Panlong (Shenzhen Daxue xuebao. Ligong ban)
Addressing issues of local optima and low convergence accuracy existed in the standard flow direction algorithm , we propose an improved flow direction algorithm by incorporating Levy flight and weed invasion strategy. Firstly, in the selection of flow direction, the newly-designed algorithm introduces Levy flight mechanism to guide the flow along optimal flow positions and prevent it getting stuck in local optima. Secondly, breed, spread and compete operations are conducted to each generation of water flow by using invading weed strategy to increase the diversity of water flow, expand the search scope and further improve the overall optimization capabilities. Finally, the improved flow direction algorithm is implemented for the coverage optimization of wireless sensor networks, and its performance is compared with that of the standard flow direction algorithm and other improved algorithms. Simulation results show that the improved flow direction algorithm achieves a coverage rate of 98.52%, surpassing both the standard flow direction algorithm and other enhanced algorithms. This improvement leads to a more uniform node distribution and lower deployment costs.